Financing, Pricing, and Utilization of Pharmaceuticals in China : The Road to Reform - World Bank (Washington, DC, 2017)
This paper examines the financing, pricing, and utilization of pharmaceuticals in China the pharmaceutical system as it has evolved, and some changes that would improve it in the context of the national health reform process. The present paper builds upon earlier critical reviews and other papers published in the series china health policy notes. The paper is divided into four parts. The first section provides an overview of the Chinese pharmaceutical market: how the sector has grown; China's position in the global market; and size, composition, and trends in the domestic market. The second section examines the evolution and status of China's system of essential medicines, an area emphasized in the government's health reform plan announced in April 2009. It shows how the use of essential medicines has evolved over the two decades since the idea was formally adopted, and discusses why practice has fallen far short of the ideal. The third section looks at the issue that dominates today's debate: managing high pharmaceutical costs. It reviews the components of drug pricing, underscoring the argument that there is considerable scope for reducing prices. It looks at government attempts to control drug prices, and suggests why they did not succeed. Finally, the fourth section suggests measures to re-chart the path to reform.